Legal Protection For Online Media Consumers In Default Cases - Stevanny Rehulina Purba; Heru Suyanto (Dinasti Research, 2024)
This research aims to know and understand the form of default by the seller to the buyer in the online buying and selling contract, as well as to know and describe the legal protection for buyers in the event that the seller defaults on the online buying and selling contract. type of normative juridical research with a statute approach and conceptual approach Data collection from secondary materials is carried out by library method and analyzed using qualitative methods. The result of this research is the occurrence of default by the seller to the buyer in the online sale and purchase contract due to the non-fulfillment of obligations by the seller, causing losses to the buyer. The seller breaks the promise as written in the contract. The seller's right is to receive payment according to the agreed price and time, while the seller's obligation is to deliver goods or services according to the agreement. The forms of default in online buying and selling agreements, viewed from the seller's side, include sending goods but not in accordance with what has been agreed upon and the absence of accountability. The form of prevention taken is what has actually been regulated in the UU-ITE, KHUPer, PP and other laws and regulations as a form of legal protection for consumers. As a form of understanding and knowing the legal protection of consumers who default on transaction users through online media focuses on legal settlements against default of transaction users through online media.